The Role of Telemedicine on Ecuador During the COVID-19 Crisis: A Perspective from a Volunteer Physician - Nicolalde, Bryan (International Journal of Medical Students, 2020)
Ecuador is one of the most affected countries of COVID-19 in Latin American. The government invited physicians to become a volunteer to attend call center and practice telemedicine in order to relief an oversaturated health system. Due lack of availability and digital illiteracy the government implement just standard calls. The difficulties that can be faced are secondary to establishing the severity of a patient only with subjective measures and to achieving effective coordination of telemedicine with public health systems. The role played by the doctor during this crisis is fundamental from the educational, preventive and psychological point of view.